Effects of assessment method (real-time versus video-recorded) on a validated pain-altered behavior scale used in castrated piglets - Trindade, Pedro Henrique Esteves [UNESP]; Lopez-Soriano, Magdiel; Merenda, Victoria Rocha; Tomacheuski, Rubia Mitalli; Pairis-Garcia, Monique Danielle (Springer Nature, 2023)
We aimed to compare two assessment methodologies (real-time vs. video-recorded) using the Unesp-Botucatu Pig Composite Acute Pain Scale (UPAPS) in piglets before and after castration. Twenty-nine male piglets were castrated. Four observers scored the UPAPS over three perioperative timepoints of castration following two assessment methodologies. In real-time assessments, the observers were in-person observing the piglets in front of the pen. After two weeks, the observers did video-recorded assessments randomizing piglets and timepoints. Modeling was conducted to compare the UPAPS and each pain-altered behavior between methodologies. Intraclass correlation coefficient (ICC), Bland–Altman, and Lin’s concordance correlation coefficient (CCC) were conducted to investigate agreement between methodologies. UPAPS was statistically equivalent between methodologies (P = 0.4371). The ICC for each method was very good (0.85 to 0.91). The agreement of the UPAPS assessed between methodologies had minimal bias (− 0.04), no proportion bias, and 53% of the assessments presented a perfect agreement. However, CCC of the UPAPS was moderate (0.65), and only one pain-altered behavior (“presents difficulty in overcoming obstacles or other animals”) occurred more in real-time assessments (P = 0.0444). In conclusion, piglet pain assessment by UPAPS can be conducted in real-time based on a suitable agreement between the real-time and video-recorded assessment methods.